Bats of the Paranã River Valley, Tocantins and Goiás states, Central Brazil - Bezerra, Alexandra M. R.; Marinho-Filho, Jader (Zootaxa, 2010)
The Valley of the Paranã River is located in the states Tocantins and Goiás, Brazil. This region is inserted in the transitional area between the Cerrado, a Neotropical Savanna Hotspot, and the Amazon and Caatinga biomes. Transitional zones are alleged to be characterized by high species richness due to the overlap of species distributional ranges, and by a high level of endemism provided by the uniqueness of these regions. The aim of this study was to survey the chiropteran fauna of the Paranã River Valley, analyzing the species composition, richness and endemism, and to contribute with the increasing knowledge of the mammalian fauna of the Cerrado, since the northern portion of this biome is one of the most poorly known. We surveyed the bats using both mist net and hand capture methods, totalizing 16, 650 m2 net-hour. A total of 23 species was surveyed, being five new records for Goiás state, nine new records for Tocantins state, and 10 species considered rare or threatened. The locality Alvorada do Norte, in northeastern Goiás state, surrounded by karstic formations showed the highest number of species, highest number of new records, and of species of special interested.